Underneath the Bragg peaks structural analysis of complex materials - Egami, Takeshi (Pergamon materials series, 2003)
* Introducing a unique method to study the atomic structure of nano-materials * Award winning research. Takeshi Egami received the 2003 Eugene Bertram Warren Diffraction Physics Award for the work described in the book. This book focuses on the structural determination of crystalline solids with extensive disorder. Well-established methods exist for characterizing the structure of fully crystalline solids or fully disordered materials such as liquids and glasses, but there is a dearth of techniques for the cases in-between, crystalline solids with internal atomic and nanometer scale disorder. Egami and Billinge discuss how to fill the gap using modern tools of structural characterization. While this subject might sound rather narrow, the fact is that today this problem is encountered in the structural characterization of a surprisingly wide range of complex materials of interest to modern technology and is becoming increasingly important